TANAMAN AREN SEBAGAI TANAMAN MULTI GUNA DALAM UPAYA PENINGKATAN PENDAPATAN KELUARGA PETANI DI DESA SIALAMAN KABUPATEN TAPANULI SELATAN - Darmadi Erwin Harahap; Syawaluddin (Bajang Institute, 2021)
This community service activity aims to increase the knowledge of the farming community in understanding sugar palm plants as a multipurpose plant as an effort to increase the income of farming families in Sialaman Village, South Tapanuli Regency. Implementation This activity was carried out by means of directives and interactive dialogue related to sugar palm plants as multi-purpose plants. The response from farmers in this activity was very positive. Farmers are also very enthusiastic about asking questions. This activity is carried out with the hope of increasing public understanding about the many benefits of sugar palm plants, so that it can increase farmers' income and improve the lives of farmers' families